2002
DOI: 10.1002/chin.200222239
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Microporous Crystal 12CaO×7Al2O3 Encaging Abundant O Radicals.

Abstract: -Preparation of the title compound (space group I43d, Z = 2) from a mixture of CaCO 3 and γ-Al 2 O 3 at 1350 • C for 6 h under controlled partial pressures of O 2 and H 2 O leads to the generation of entrapped active oxygen in form of a pair of O − and O 2 − in a wide concentration range (up to 6·10 20 cm −3 ). The samples are characterized by magnetic measurements and ESR spectroscopy. It is expected that these materials provide a unique opportunity for applications. -(HAYASHI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 1 publication
1
11
0
1
Order By: Relevance
“…4a) shows an orthorhombic signal characteristic of O 2 -trapped on the Ca 2? cations in the g 2 side-on fashion within the nanocavities [45,46]. Its analysis via computer simulation allowed extraction of the g tensor components (g zz = 2.078, g yy = 2.012, and g xx = 2.005), which are in a nice accordance with predictions of the Känzig-Cohen …”
Section: Principal Mechanisms Of O 2 2 Formation and Varieties Of Supsupporting
confidence: 56%
“…4a) shows an orthorhombic signal characteristic of O 2 -trapped on the Ca 2? cations in the g 2 side-on fashion within the nanocavities [45,46]. Its analysis via computer simulation allowed extraction of the g tensor components (g zz = 2.078, g yy = 2.012, and g xx = 2.005), which are in a nice accordance with predictions of the Känzig-Cohen …”
Section: Principal Mechanisms Of O 2 2 Formation and Varieties Of Supsupporting
confidence: 56%
“…[10] Various anions (F -, Cl -, OH -, O -, and O À 2 ) can replace O 2-ions in the cage. [11][12][13][14] Recent results indicate that a part of the O 2-ions in the cage can be removed under reducing conditions (carbon container) at high temperatures producing a nonstoichiometric oxide with high electronic conductivity. [15] The X-ray diffraction pattern of Ca 12 Al 14 O 33 exposed to reducing conditions was almost identical to that of the sample heated in dry oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, results from flow-cytometry reported by Hewitt et al (2001) supported this theory. Although the mechanism of active oxygen species generation from alkaline earth metal oxides, such as CaO, was not explored, Hayashi et al (2002) recently reported that a solid solution of CaO and alumina could generate a large amount of active oxygen species using ESR measurement. Active oxygen generated from HSSP, which contains CaO as the main component, may also contribute to disinfection efficacy.…”
Section: Resultsmentioning
confidence: 99%